2021
DOI: 10.1007/s00062-021-01015-3
|View full text |Cite
|
Sign up to set email alerts
|

DCE-MRI in Glioma, Infiltration Zone and Healthy Brain to Assess Angiogenesis: A Biopsy Study

Abstract: Purpose To explore the focal predictability of vascular growth factor expression and neovascularization using dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) in glioma. Methods 120 brain biopsies were taken in vital tumor, infiltration zone and normal brain tissue of 30 glioma patients: 17 IDH(isocitrate dehydrogenase)-wildtype glioblastoma (GBM), 1 IDH-wildtype astrocytoma °III (together prognostic group 1), 3 IDH-mutated GBM (group 2), 3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The modified Response Assessment Neuro Oncology (RANO) criteria is used to evaluate for tumor growth versus pseudo progression and is especially helpful for longitudinal follow-up during adaptive clinical trials to mitigate false negative and false positive results [37]. Other advanced techniques to quantify vascular permeability with focused ultrasound studies include DCE MRI [38] and contrastenhanced (CE) T1 digital subtraction maps [39]. Dynamic susceptibility contrast (DSC) MRI also allows for quantification of blood volume, flow, and vessel size [40,41].…”
Section: Radiologic Assessmentmentioning
confidence: 99%
“…The modified Response Assessment Neuro Oncology (RANO) criteria is used to evaluate for tumor growth versus pseudo progression and is especially helpful for longitudinal follow-up during adaptive clinical trials to mitigate false negative and false positive results [37]. Other advanced techniques to quantify vascular permeability with focused ultrasound studies include DCE MRI [38] and contrastenhanced (CE) T1 digital subtraction maps [39]. Dynamic susceptibility contrast (DSC) MRI also allows for quantification of blood volume, flow, and vessel size [40,41].…”
Section: Radiologic Assessmentmentioning
confidence: 99%
“…High-grade gliomas (such as GBM) are characterised by disorganised vasculature, immature endothelial cells and increased permeability, with the margins associated with increased microvessel density (MVD) and neovascularization [ 28 ]. Studies of the tissue surrounding the enhancing portion of GBM have shown correlations between DCE-MRI parameters and expression of hypoxia-related proteins such as vascular endothelial growth factor-A (VEGF-A), suggesting that the DCE-MRI changes could be detecting regions of tissue hypoxia [ 12 , 13 , 29 ]. The finding of discordant DCE-MRI and 18 F-fluciclovine PET volumes outside of the Gd-T1 hyperintense regions raises the question of whether the two approaches could be used in a complementary fashion, potentially highlighting regions of increased glioma cellular density and areas of increased tissue hypoxia and therefore highlight different tumour niches.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic contrast-enhanced perfusion-weighted imaging (DCE) MRI has also been used to investigate vascular changes in glioblastoma (GBM), and studies have shown a correlation with tumour infiltrating beyond the enhancing margin and with markers of tissue hypoxia and neoangiogenesis [ 2 , 12 , 13 ]. In addition, some DCE-MRI quantitative biomarkers such as interstitial volume (v e ) may correlate with overall survival (OS) and tumour-associated microvascular proliferation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have proved that magnetic resonance imaging is of great value in the metabolic and physiological processes of gliomas, such as DWI [20]. DTI [21], MRS [22,23], DSC MRI [24,25], and DCE MRI have achieved good results in the evaluation of glioma grading [26,27]. In addition, the evaluation of tumor heterogeneity through imaging is of great benefit to guide the clinic, especially in the individualized treatment of gliomas.…”
Section: Discussionmentioning
confidence: 99%